Unique genomic organization of a novel Avipoxvirus detected in turkey (Meleagris gallopavo) - Bányai, Krisztián; Palya, Vilmos; Dénes, Béla; Glávits, Róbert; Ivanics, Éva; Horváth, Balázs; Farkas, Szilvia L.; Marton, Szilvia; Bálint, Ádám; Gyuranecz, Miklós; Erdélyi, Károly; Dán, Ádám (Infection, genetics and evolution, 2015)
•The whole genome sequence of a novel avipoxvirus that emerged in Hungary during 2011 in turkey flocks is described in this study.•The genome size measured approx. 188.5kbp.•Phylogenetic analysis of the 4b and DNA polymerase genes classified this strain into a novel genetic clade. Avipoxviruses are emerging pathogens affecting over 200 bird species worldwide. Genetic characterization of avipoxviruses is performed by analysis of genomic regions encoding the 4b and DNA polymerase. Whole genome sequence data are limited to a few avipoxvirus isolates. Based on phylogenetic analysis three major genetic clades are distinguished. In this study we report a novel avipoxvirus strain causing skin lesions in domestic turkey. The virus was identified in Hungary during 2011 in a flock of turkey vaccinated against avipoxvirus infection. The genome of the isolated strain, TKPV-HU1124/2011, was uniquely short (∼188.5kbp) and was predicted to encode reduced number of proteins. Phylogenetic analysis of the genes encoding the 4b and DNA polymerase separated TKPV-HU1124/2011 from other turkey origin avipoxviruses and classified it into a new genetic clade. This study permits new insight into the genetic and genomic heterogeneity of avipoxviruses and pinpoints the importance of strain diversity in vaccine efficacy.